IMPLEMENTASI UANG SESERAHAN NIKAH PADA ADAT ISTIADAT MASYARAKAT KAB. TULANG BAWANG PRESPEKTIF MADZHAB SYAFI’I - A. Fathul Khobir, Ahmad Zuhairuz Zaman (UAS PRESS, 2023)
One of the series in the traditional marriage of the Kampung Pasiran Jaya community is offering. Seserahan is the gift of the groom to the woman as a form of seriousness from the man to the woman. In the handover process, luggage is also included in the form of a set of bedding, goats, food, kitchen utensils, a set of cooking utensils, clothes, money, makeup tools and others. This study uses a sociological normative approach with a case study type of research. The results of this study conclude that: (1) The presentations carried out in Pasiran Jaya Village today are different from the old days. Seserahan is a tradition of giving goods that have been agreed upon by both parties of the bride and groom without any element of coercion. This tradition has experienced a shift in dynamics, but there are still many residents of Kampung Pasiran Jaya who suppress the amount of the handover money. (2) According to Madzab Syafi'i, the status of the gift is only as a gift to the prospective wife before entering into a contract. However, the man has the right to withdraw the gift if the marriage contract fails.